2019
DOI: 10.1038/s41598-019-42040-0
|View full text |Cite
|
Sign up to set email alerts
|

TGFβ2-induced senescence during early inner ear development

Abstract: Embryonic development requires the coordinated regulation of apoptosis, survival, autophagy, proliferation and differentiation programs. Senescence has recently joined the cellular processes required to master development, in addition to its well-described roles in cancer and ageing. Here, we show that senescent cells are present in a highly regulated temporal pattern in the developing vertebrate inner ear, first, surrounding the otic pore and, later, in the otocyst at the endolymphatic duct. Cellular senescen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
37
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(41 citation statements)
references
References 44 publications
2
37
1
1
Order By: Relevance
“…Given that developmental senescence is found in some of the tissues that are most susceptible to mutation and birth defects, it is tempting to speculate that mis-regulation of senescence may be causally involved. Indeed, a number of studies in mouse models, including mice deficient in p63 (Keyes et al, 2005), PASG (Hells; Sun et al, 2004) and Brca1 (Cao et al, 2003), have shown how mutations that affect embryonic development also induce aberrant senescence, whereas recent studies using senolytics demonstrate how mis-regulation of the normal developmental process can cause patterning defects (Gibaja et al, 2019). A better appreciation of this link will further our understanding of senescence and its role in human health and disease.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Given that developmental senescence is found in some of the tissues that are most susceptible to mutation and birth defects, it is tempting to speculate that mis-regulation of senescence may be causally involved. Indeed, a number of studies in mouse models, including mice deficient in p63 (Keyes et al, 2005), PASG (Hells; Sun et al, 2004) and Brca1 (Cao et al, 2003), have shown how mutations that affect embryonic development also induce aberrant senescence, whereas recent studies using senolytics demonstrate how mis-regulation of the normal developmental process can cause patterning defects (Gibaja et al, 2019). A better appreciation of this link will further our understanding of senescence and its role in human health and disease.…”
Section: Discussionmentioning
confidence: 99%
“…This was primarily based on studies describing senescent cells in mouse embryos (Muñoz-Espin et al, 2013;Storer et al, 2013). However, cells bearing some or many features of senescence have also been described in human (Muñoz-Espin et al, 2013), chicken (Storer et al, 2013;Gibaja et al, 2019), quail (Nacher et al, 2006), Xenopus (Davaapil et al, 2017), axolotl (Davaapil et al, 2017;Villiard et al, 2017), zebrafish (Villiard et al, 2017) and naked mole rat (Zhao et al, 2018) embryos (Table 1).…”
Section: Developmental Senescencementioning
confidence: 99%
See 1 more Smart Citation
“…TGF-β1 levels were increased with aging (33), and in the ante-and postmortem sera from patients with AD, as well as in the postmortem cerebrospinal fluid of patients with AD (34). Furthermore, TGF-β is secreted as part of the SASP (3), and it can trigger senescence in neighboring cells (3,35,36). Our current study findings demonstrated that the TGF-β1-SMAD2/3 pathway is induced in 5xFAD astrocytes, and that inhibition of this pathway can reduce the expression of the senescence phenotype.…”
Section: Discussionmentioning
confidence: 99%
“…As we previously described, TGFβ2 is a potent regulator of cellular senescence during inner ear development, which has been proven to be an essential process for proper morphogenesis of the endolymphatic duct (Gibaja et al, 2019). We, therefore, aimed to investigate whether developing AVG neuroblasts in HH19 stages underwent cellular senescence regulated by TGFβ2.…”
Section: Tgfβ Pathway Does Not Induce Senescence In the Avgmentioning
confidence: 99%